2018
DOI: 10.3390/bios8010025
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Biosensors to Explore the Potential of Probiotic Strains to Reduce the SOS Response and Mutagenesis in Bacteria

Abstract: A model system based on the Escherichia coli MG1655 (pRecA-lux) Lux-biosensor was used to evaluate the ability of the fermentates of eight probiotic strains to reduce the SOS response stimulated by ciprofloxacin in bacteria and mutagenesis mediated by it. Preliminary attempts to estimate the chemical nature of active components of the fermentates were conducted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 33 publications
1
17
0
Order By: Relevance
“…Whole-cell biosensors are widely used for assessing compounds' toxicity and ecological control [34,35]. Gram-positive and Gram-negative bacteria can have different sensitivities to the same toxicant.…”
Section: Discussionmentioning
confidence: 99%
“…Whole-cell biosensors are widely used for assessing compounds' toxicity and ecological control [34,35]. Gram-positive and Gram-negative bacteria can have different sensitivities to the same toxicant.…”
Section: Discussionmentioning
confidence: 99%
“…Our studies demonstrated that sporeforming probiotic organisms, obtained through solid phase fermentation, have antimutagenetic and antioxidative effects, as well as increase chicken mass and egg-laying ability [12,22,23].…”
Section: Methods Detailsmentioning
confidence: 99%
“…Lactobacilli are widely used in medicine and veterinary as probiotic bacteria (Acurcio et al, 2014;Ruzicka et al, 2016 Chistyakov et al, 2018;Mekadim et al, 2018). In addition to lactobacilli, bifidobacteria are actively used as probiotics, and they have similar properties (Saez-Lara et al, 2015;Wang et al, 2016).…”
Section: Introductionmentioning
confidence: 99%